Literature Review and Preliminary Analysis of Cassava By-products Potential Use in Particleboards - Ana Maria Denardi Piccini; Jorge Daniel de Melo Moura; Anderson Rodrigo Piccini (BioResources, 2024)
Particle panels for construction are environmentally favorable, as they allow the combination of different components (as is the case with agro-industrial waste from the production and processing of food and products derived from agricultural activities). The objective of this article is to analyze studies focused on the use of cassava by-products in the production of panels for civil construction/furniture in the last 10 years through a bibliographical survey, as well as to present a preliminary analysis of the feasibility of using cassava by-products to manufacture particle panels in their natural state. As a result, the theoretical search detected the gap created by the scarcity of published studies on the topic. On the other hand, the experimental analysis indicated the promising potential of using the cassava by-product for panel production, provided that the weaknesses initially indicated in this research can be addressed.